The use of stem cells and keratoprosthesis – special surgery types for corneal disorders (a narrative review) - Dydyk, Martyna; Sikorska, Ewa; Sikorski, Piotr; Tomaszewski, Robert; Kopacz, Dorota (Journal of Medical Science, 2024)
Corneal disease and damage can arise from various causes, including infections, corneal dystrophies, trauma and improper contact lens use. These factors can lead to corneal blindness which greatly decreases the patient’s quality of life. Although corneal transplantation is a viable treatment option for many patients, the risk of rejection after corneal transplantation remains a concern. Severe corneal damage requires special methods of treatment, which are still sought after. This narrative review aims to summarize the use of stem cells and keratoprosthesis in the treatment of corneal diseases. Stem cell therapy, particularly limbal stem cell transplantation, shows promise in corneal regenerative therapy, especially the treatment of limbal stem cell deficiency. Additionally, induced pluripotent stem cells have been successfully used in cornea transplantation, offering a novel approach to restoring vision in patients with corneal diseases. Keratoprosthesis, such as the Boston keratoprosthesis and osteo-odonto-keratoprosthesis, provides an alternative for patients who cannot undergo traditional corneal transplantation. Artificial prostheses are also an alternative to corneal transplantation in cases of extensive trauma or in the absence of donor tissue. Continued research and development in stem cell therapy and keratoprosthesis hold the potential to improve the outcomes, accessibility of corneal disease treatment and reducing the global burden of corneal blindness.
Keywords: stem cells; keratoprosthesis; corneal blindness; corneal disease; boston keratoprosthesis; osteo-odonto keratoprosthesis